Dissociative Model in Patients With Resistant Schizophrenia - Panov, Georgi (Frontiers in Psychiatry, 2022)
We studied the dissociative symptoms in patients with schizophrenia and found a link between resistance to the antipsychotic drugs used and the presence of a high degree of dissociation. We measured the dissociation with the scale for assessment of dissociative experiences and found up to 3 times higher dissociation in patients with resistance to treatment. By default, dissociative disorders are not treated with antipsychotic medications, which raises the question of reconsidering the nature of resistant schizophrenia.